Case Study of the Use of Recycled Concrete in Highway Projects - Ilham, Ilham; Ngii, Edward; One, La (Journal of Moeslim Research Technik, 2024)
The increasing demand for sustainable construction practices has led to the exploration of recycled materials, particularly in road projects. Recycled concrete not only reduces waste but also offers potential environmental and economic benefits. Understanding its effectiveness in real-world applications is essential for promoting its wider use. This study aims to evaluate the performance of recycled concrete in highway construction projects, assessing its structural integrity, cost-effectiveness, and environmental impact. It seeks to provide insights into the feasibility of using recycled materials in road infrastructure. A case study approach was employed, analyzing three highway projects that utilized recycled concrete. Data were collected through site inspections, material testing, and interviews with project managers. Key performance indicators, such as compressive strength, durability, and cost savings, were evaluated. The findings indicate that recycled concrete performed comparably to traditional concrete in terms of compressive strength and durability. Cost analysis revealed significant savings, with recycled concrete reducing material costs by an average of 15%. Environmental assessments highlighted notable reductions in carbon emissions and landfill waste. The research concludes that recycled concrete is a viable option for highway construction, offering both economic and environmental advantages. The positive outcomes from the case studies support the broader adoption of recycled materials in infrastructure projects. Future studies should focus on long-term performance and the development of guidelines for integrating recycled concrete in various construction applications.